2019
DOI: 10.1088/1475-7516/2019/06/035
|View full text |Cite
|
Sign up to set email alerts
|

Relativistic bias in neutrino cosmologies

Abstract: Halos and galaxies are tracers of the underlying dark matter structures. While their bias is well understood in the case of a simple Universe composed dominantly of dark matter, the relation becomes more complex in the presence of massive neutrinos. Indeed massive neutrinos introduce rich dynamics in the process of structure formation leading to scale-dependent bias. We study this process from the perspective of general relativity employing a simple spherical collapse model. We find a characteristic signature … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…Anyhow, Refs. [56,57] have recently demonstrated that even neutrino bias is not sensitive to the specific mass hierarchy (see however Ref. [58]).…”
Section: Changes To the Lss Observables -Galaxy Clustering And Weak L...mentioning
confidence: 99%
“…Anyhow, Refs. [56,57] have recently demonstrated that even neutrino bias is not sensitive to the specific mass hierarchy (see however Ref. [58]).…”
Section: Changes To the Lss Observables -Galaxy Clustering And Weak L...mentioning
confidence: 99%
“…from Euclid [230] or DESI [231]. We also stress that the scale-dependent bias we are considering here is relevant on small scales (large k), and is totally distinct from the spurious scale-dependence studied by some of us in [232], appearing on large scales (small k) in the presence of massive neutrinos if the bias itself is not correctly defined (see also [201,203,233,234]). The rest of this work is then structured as follows.…”
Section: Introductionmentioning
confidence: 70%
“…Nonetheless, this distinction is not important given the sensitivity of current galaxy clustering data, and will only become relevant with upcoming data (e.g. from Euclid or DESI), as discussed for instance in [201,203,[232][233][234].…”
Section: Galaxy Biasmentioning
confidence: 99%
“…(2.8) [26,29,30] that will therefore be scale-dependent. The analytical calculation of [26,31,50], as well as the results from N-body simulations [30] indicate that b ν O(1)f ν and is only important on linear scales k ≤ 0.01 h/Mpc. Being so small, this form of scale-dependent bias is not expected to add much in terms of constraining power on massive neutrinos.…”
Section: Scale-dependent Effects From Massive Neutrinosmentioning
confidence: 83%

Weighing neutrinos with the halo environment

Banerjee,
Castorina,
Villaescusa-Navarro
et al. 2019
Preprint